(untitled) (Research, Society and Development, 2022)
At the beginning of 2020, the Covid-19 pandemic emerged, which affected all segments of the world economy. The out-of-home food sector was one of the most impacted economically and financially, due to restrictions and social distancing. In view of this, the objective of this research is to analyze the impacts of the Covid-19 pandemic on the economic-financial management of a restaurant-pizzeria in the municipality of Cacoal. The study has a qualitative-quantitative approach, of an exploratory nature. Through the comparative analysis of the indicators between the years 2016 and 2020, it was found that the pandemic was reflected in the financial reports with a considerable reduction in net sales revenue in 2020 compared to previous years. Despite this reduction, the company points to the ability to meet its commitments, but has used third-party capital to maximize liquidity. The company also demonstrates concerns and measures so that the impacts of the pandemic do not directly affect its financial and operational performance.